Health providers' compliance with pregnant women's Bill of Rights in labor and delivery in Iran - Vajihesadat Mirlohi; Soheila Ehsanpour; Shahnaz Kohan (Wolters Kluwer Medknow Publications, 2015)
Background: Delivery is one of the most important crises with mental, social, and deep emotional dimensions in women's life. Health providers' respect to pregnant women's Bill of Rights, as an important component of providing humanistic and ethical care, is of utmost importance. This study aimed to determine health providers' compliance with the pregnant women's Bill of Rights in labor and delivery and some of its related factors in 2013. Materials and Methods: This descriptive, cross-sectional study was carried out on the subjects selected through census sampling (N = 257) from among the healthcare providers working in the labor rooms of four educational hospitals. The data were collected by a self-reported questionnaire whose validity and reliability were established. Data were analyzed through descriptive and inferential statistics. Results: The compliance with pregnant women's Bill of Rights was found to be at a very high level in 22.8% of the midwifery students, 28.6% of the residents of obstetrics and gynecology, 21.9% of the interns, 50% of the obstetrics and gynecology faculty members (professors), and 31.9% of the midwives. There was a significant difference between the five groups of service providers in terms of overall compliance with mothers' rights (P = 0.002). The results showed that the residents in higher years of education (P = 0.001), midwifery students in higher semesters (P = 0.001), midwives with more work experience (P < 0.001), and personal experience of being hospitalized in labor room (P < 0.001) had a higher compliance with Bill of Rights. Meanwhile, there was no significant difference in compliance with Bill of Rights between labor and age (P = 0.82). Conclusions: The results showed that the health providers' compliance with the pregnant women's Bill of Rights was not acceptable in the labor room. Therefore, necessary actions are needed to remove the barriers against pregnant women's compliance of Bill of Rights and to facilitate the compliance with it in hospitals.